2004
DOI: 10.1111/j.1365-2044.2004.03994.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of intravenous infusion of ephedrine or mephentermine for management of hypotension during spinal anaesthesia for Caesarean section

Abstract: SummaryThis study compared the effects of intravenous infusions of ephedrine and mephentermine for maintenance of maternal arterial pressure and neonatal outcome in pregnant women receiving subarachnoid block for lower segment Caesarean section. Sixty patients who developed hypotension following subarachnoid block for Caesarean section were randomly divided into two groups of 30 each to receive an intravenous infusion of ephedrine or mephentermine. Hypotension was defined as a decrease in systolic blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…: SCID-CV) were not applied for the diagnosis of depression. This is also a limitation of the study by Margis et al 2 The total score in the PDQ-39 and its subscales/dimensions strongly correlated with the total score in the GDS-15. The group of patients with current depression (GDS-15 ≥ 8) had higher scores (p < 0.0001) in the PDQ-39 and its dimensions (Table 1).…”
Section: Qualidade De Vida E Sintomas Depressivos Na Doença De Parkinsonmentioning
confidence: 87%
See 3 more Smart Citations
“…: SCID-CV) were not applied for the diagnosis of depression. This is also a limitation of the study by Margis et al 2 The total score in the PDQ-39 and its subscales/dimensions strongly correlated with the total score in the GDS-15. The group of patients with current depression (GDS-15 ≥ 8) had higher scores (p < 0.0001) in the PDQ-39 and its dimensions (Table 1).…”
Section: Qualidade De Vida E Sintomas Depressivos Na Doença De Parkinsonmentioning
confidence: 87%
“…Thus, we have read with great interest the article by Margis et al in which the authors assessed the influence of depressive symptoms on the quality of life of PD patients. 2 The authors observed that the Geriatric Depression Scale (GDS) score was positively associated with the total score in the World Health Organization Quality of Life Assessment for older adults and five of its six domains.…”
Section: Qualidade De Vida E Sintomas Depressivos Na Doença De Parkinsonmentioning
confidence: 99%
See 2 more Smart Citations
“…Post spinal hypotension (PSH): Reduction of systolic blood pressure from baseline by 20% following spinal anesthesia [43,44].…”
Section: Operational Definitionsmentioning
confidence: 99%